Development Of Traditional Para Fruit Game-Based Learning Media For Integer Counting Material At Sdn Selat Gelam District - Bambang Herianto; Tety Kurmalasari; Zaitun; Abdul Malik; Encik Abdulhajar (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The rapid development of the 21st century requires teachers to be creative in integrating local culture into the classroom, especially in abstract subjects like mathematics. This study aims to develop learning media based on the traditional game of "Buah Para" (rubber fruit) for integer arithmetic operations for elementary school students in the Selat Gelam District. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through validation sheets, teacher and student response questionnaires, and learning outcome tests. The validation results from material and media experts showed that the developed media was in the "Very Valid" category. Practicality tests conducted with teachers and students also indicated that the media was "Very Practical" to use. Furthermore, the effectiveness test showed a significant increase in students' understanding of integers after using the Buah Para game media. It can be concluded that the development of this ethnomathematics-based media is effective in improving the quality of mathematics learning while preserving local wisdom